Association of Mandible Anatomy with Age, Gender, and Dental Status: A Radiographic Study. (18th December 2013) - Chole, Revant H.; Patil, Ranjitkumar N.; Balsaraf Chole, Swati; Gondivkar, Shailesh; Gadbail, Amol R.; Yuwanati, Monal B.
Abstract : Introduction . Gonial angle and antegonial region are important landmarks in mandible which is influenced by gender, age, and dental status. The objective of this study was to evaluate the gonial angle, antegonial angle, and antegonial depth and to investigate their relationship to gender, age group, and dental status. Materials and Methods . A total of 1060 panoramic radiographs were evaluated: the dentulous group, 854 subjects and the edentulous group, 206 subjects. The patients were grouped into six age groups of 10-years each. Gonial angle, antegonial angle, and antegonial depth were measured from panoramic radiographs. Results and Discussion . Corelation of age with gonial angle, antegonial angle and antegonial depth was not significant. Significant difference in mandibular angle was found between males and females. Males had significantly smaller antegonial angle and greater antegonial depth than females. Significant difference was found for gonial angle, antegonial angle, and antegonial depth between right and left sides of mandible. Conclusion . Gonial angle, antegonial angle, and antegonial depth can be implicated as a forensic tool for gender determination but not suitable for age determination.